Datos sobre cinco plantas poco conocidas en el País Vasco y Navarra - Berastegui, Asun; Campos, Juan Antonio; Darquistade, Ainhoa (Lazaroa, 2001)
In this paper floristic, chorological, ecological and phytosociological data are reported about 5 little known taxa from the Basque Country and Navarre. The regions considered aee the provinces of Álava, Guipúzcoa, Navarre and Vizcaya. Besides new records, bibliographical locations in the study area were compiled for each species.